2011
DOI: 10.3109/01676830.2010.535952
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Dacryocystorhinostomy in Acute Dacryocystitis: A Multicenter Case Series

Abstract: EndoDCR surgery performed early in AD led to rapid resolution of the condition in all cases and was associated with subsequent anatomical and functional success in 94.4% of cases. Early endoDCR surgery in the context of AD and the potential associated health economic benefits are worth further consideration and study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 23 publications
(46 reference statements)
4
67
0
3
Order By: Relevance
“…2 However, the total health costs of our approach, including hospitalization time and postoperative surveillance, were not assessed, and the costeffectiveness ratio of our protocol should be better defined, possibly in a prospective way.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, the total health costs of our approach, including hospitalization time and postoperative surveillance, were not assessed, and the costeffectiveness ratio of our protocol should be better defined, possibly in a prospective way.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have proposed dacryocystorhinostomy, most recently using endoscopic dacryocystorhinostomy, as a direct treatment for acute dacryocystitis. 20 In their multicenter retrospective review of 18 patients with acute dacryocystitis treated via endo-DCR, Madge et al reported a 94.4% success with an average of 12 months' follow-up. It should be noted, though, that all patients received either oral or intravenous antibiotics for an average of 5 days prior to surgery, with 66.7% having documented clinical improvement prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the dacryocystorhinostomy, reports suggest that endoscopic approach is more successful with success rates ranging from 82% to 95% as compared to external approach dacryostorhinostomy [7] . Placement of silicone stent intraoperatively through both the canaliculi is having multiple schools of thought-in patient selection, duration of placement of the stent and outcome.…”
Section: Introductionmentioning
confidence: 99%